Kekuatan Angka-Angka Perusahaan Dalam Pemilihan Kantor Akuntan Publik - Ricky, Ricky Bryan D.P. Tampubolon; Rabiyahtul Santiya; Indy Ramadhani Putri Pountung; Muhammad Rasyiq Taqiyudin Syauqi; Ikhsan Dwi Jantika; Adhitya Figuerra Yuscrates (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2025)
This study examines the influence of cash volume, retained earnings, and total assets on the selection of Public Accounting Firms (KAP) by energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2024. Using purposive sampling, a total of 79 companies were analyzed with Multiple Linear Regression. The simultaneous test (F Test) shows that the three financial variables significantly affect KAP selection (F calculated = 6.785; Sig. < 0.001). However, the model’s explanatory power remains limited with an R-squared of 0.213, indicating that only 21.3% of the variation in KAP selection is explained by these variables. Meanwhile, the partial test (T Test) reveals that Cash Volume (Sig. = 0.862), Retained Earnings (Sig. = 0.233), and Total Assets (Sig. = 0.116) do not significantly influence KAP selection individually. These findings suggest that although financial indicators collectively contribute to the decision, energy companies tend to rely more on qualitative managerial judgments and non-financial factors beyond the regression model.